Forward‐wave directional coupler based on slow‐wave coupled microstrip lines. Issue 14 (9th September 2019) - Luong, Duc‐Long; Acri, Giuseppe; Podevin, Florence; Vincent, Didier; Pistono, Emmanuel; Serrano, Ariana; Ferrari, Philippe
Abstract : This study presents the design of a forward‐wave directional coupler based on slow‐wave coupled microstrip lines realised in a multilayered printed circuit board technology. Thanks to the concept of slow‐wave, a high difference between the even‐ and odd‐mode phase velocities can be inherently achieved. Hence, by choosing adequate even‐ and odd‐mode characteristic impedances close to 50 Ω, reduced‐length forward couplers can be designed. As a proof of concept, a 0 dB forward coupler operating at 4.5 GHz is proposed. It exhibits a very high coupling of 0.56 dB at the centre frequency and a very large bandwidth of 43%, corresponding to 10 dB of isolation. A length miniaturisation of 84% is obtained as compared to the standard microstrip, leading to a total surface area of 0.132 λ g 2, the smallest one reported so far.